Proceedings of the 2001 International Symposium on Physical Design 2001
DOI: 10.1145/369691.369769
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming wireload model uncertainty during physical design

Abstract: The advent of deep sub-micron technologies has created a number of problems for existing design methodologies. Most prominent among them is the problem of timing closure, whereby design time is dramatically increased due to iterations between gate-level synthesis and physical design. It is well known that the heart of this problem lies in the use of wireload models based on wirelength statistics from legacy designs. Some technology projections in [3] have suggested that wireload models will remain effective to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…In recent publications, it has been shown that interconnect delay starts to dominate in deep submicron designs [19]. However, we should clarify that De j in formula (8) is not the commonly referred interconnect delay, which is the part of the gate delay resulting from driving the interconnect/wire capacitance.…”
Section: The Capacitive Load and Delay Modelsmentioning
confidence: 96%
“…In recent publications, it has been shown that interconnect delay starts to dominate in deep submicron designs [19]. However, we should clarify that De j in formula (8) is not the commonly referred interconnect delay, which is the part of the gate delay resulting from driving the interconnect/wire capacitance.…”
Section: The Capacitive Load and Delay Modelsmentioning
confidence: 96%
“…
At the 250nm technology node, interconnect delays account for over 40% of worst delays [12]. Transition to 130nm and below increases this figure, and hence the relative importance of timing-driven placement for VLSI.
…”
mentioning
confidence: 99%
“…average) wirelength objective is the use of max instead of Σ 12. Quadratic placements work well in practice and can be produced very quickly; faster/better approaches are possible.…”
mentioning
confidence: 99%
“…It is being argued however that for very deep submicron technologies it is not adequate any more (see for example [5]). The limitation arises from the fact that wire delays do not scaled with technology as much as gate delays, so for very fine geometries they are dominant.…”
Section: Static Timing Analysis and Post-layout Optimizationmentioning
confidence: 99%